PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING CTL TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V SD NEGERI 158 PALEMBANG - Putri Nabila Yunasli; Al Ihwanah; Jadidah, Ines Tasya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) approach on students’ learning motivation in the subject of Natural and Social Sciences (IPAS) in Grade V at SD Negeri 158 Palembang. This research employed a quantitative approach using a quasi-experimental method with a one group pretest–posttest design. The research subjects were all students of class VA at SD Negeri 158 Palembang, totaling 28 students, consisting of 14 male students and 14 female students. Data collection techniques included learning motivation questionnaires, observation, and documentation. Data analysis was conducted using descriptive and inferential statistics with the assistance of SPSS software, including the Kolmogorov–Smirnov normality test, paired sample t-test, and effect size calculation using Cohen’s d formula. The results showed that the average students’ learning motivation score before the implementation of the CTL approach was 60.50, which increased to 81.86 after the implementation. The results of the paired sample t-test indicated a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning that there was a significant effect of the CTL approach on students’ learning motivation. Furthermore, the effect size analysis resulted in a Cohen’s d value of 1.70, which falls into the category of a large effect. Therefore, it can be concluded that the Contextual Teaching and Learning (CTL) approach has a significant and effective impact on improving students’ learning motivation in the IPAS subject for Grade V students at SD Negeri 158 Palembang.